Indikasi Perilaku Breeding Elang Brontok (Nisaetus cirrhatus) Di Pusat Konservasi Elang Kamojang - Akbar, Rahmat Taufiq Mustahiq; Hamzah, Fadiya Muafa (BEST Journal (Biology Education, Sains and Technology), 2023)
Eagle is one of the animals that can be used as an indicator of environmental health because it has a high level of sensitivity to the environment. The loss of the eagle population in nature will cause ecosystem changes due to disruption of food webs. The Brontok Eagle (Nisaetus cirrhatus) is a type of eagle which according to the IUCN is classified as the least concern category, its existence in nature is not easy to find due to poaching and habitat destruction. Kamojang Eagle Conservation Center (PKEK) is a conservation organization whose function is to rehabilitate the eagles that have been kept. This research was conducted to find out indications of the breeding behavior of bald eagles in PKEK and to find out the differences in the breeding behavior of bald eagles in PKEK and eagles in nature. The method used is scan sampling with 5 minute intervals combined with the ad-libitum method. Based on the observations, the following proportions were obtained, 65% standing alone, 24% perched together, 8% flying and 3% making sounds. Based on these data, indications of breeding behavior have been observed, but it has not yet become the dominant behavior. The indications of observed breeding behavior were perched together. There is a difference in mating behavior between the Brontok eagles in PKEK and the eagles in nature, that is, they do not observe the behavior of flying together. Keywords: Breeding, Brontok eagle, Conservation